ChemInform Abstract: 25th Anniversary Article: A Decade of Organic/Polymeric Photovoltaic Research. Issue 5 (4th February 2014) - Dou, Letian; You, Jingbi; Hong, Ziruo; Xu, Zheng; Li, Gang; Street, Robert A.; Yang, Yang
Abstract Review: 292 refs.